Association of Class II Histone Deacetylases with Heterochromatin Protein 1: Potential Role for Histone Methylation in Control of Muscle Differentiation - Zhang, Chun Li (American Society for Microbiology, 2002)
Class II histone deacetylases (HDACs) 4, 5, 7, and 9 repress muscle differentiation through associations with the myocyte enhancer factor 2 (MEF2) transcription factor. MEF2-interacting transcription repressor (MITR) is an amino-terminal splice variant of HDAC9 that also potently inhibits MEF2 transcriptional activity despite lacking a catalytic domain. Here we report that MITR, HDAC4, and HDAC5 associate with heterochromatin protein 1 (HP1), an adaptor protein that recognizes methylated lysines within histone tails and mediates transcriptional repression by recruiting histone methyltransferase. Promyogenic signals provided by calcium/calmodulin-dependent kinase (CaMK) disrupt the interaction of MITR and HDACs with HP1. Since the histone methyl-lysine residues recognized by HP1 also serve as substrates for deacetylation by HDACs, the interaction of MITR and HDACs with HP1 provides an efficient mechanism for silencing MEF2 target genes by coupling histone deacetylation and methylation. Indeed, nucleosomal histones surrounding a MEF2-binding site in the myogenin gene promoter are highly methylated in undifferentiated myoblasts, when the gene is silent, and become acetylated during muscle differentiation, when the myogenin gene is expressed at high levels. The ability of MEF2 to recruit a histone methyltransferase to target gene promoters via HP1-MITR and HP1-HDAC interactions and of CaMK signaling to disrupt these interactions provides an efficient mechanism for signal-dependent regulation of the epigenetic events controlling muscle differentiation.